Subject of the contract for travel services - Чуднов, Василь Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article deals with subject of the contract for travel services from positions of adaptation of thenational legislation and the needs of its universalization and harmonization. At comparison of the concepts «tourism product» and «travel services» priority is given to the second. At the same time the subject of suchcontract is indicated as complex and mixed.